RESPON DAN EKSPEKTASI GURU PAMONG SEKOLAH MITRA TERHADAP KOMPETENSI KEGURUAN MAHASISWA PPLK PROGRAM STUDI PENDIDIKAN AGAMA ISLAM FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN RADEN FATAH PALEMBANG - Muhammad Fauzi; Elly Manizar; Sofyan Sofyan (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2017)
The idea of this study appear based on that de facto Prodi PAI Faculty Tarbiyah and Teaching (FITK) UIN Raden Fatah, who scored the candidate GPAI by decree of the National Accreditation Board of Higher Education (BAN-PT) in 2000, bears the title of accreditation B, and now has increases with the predicate of accreditation A based SK BAN-PT Number: 182 / SK / BAN-PT / Akres / S / VI / 2014. Of course, the conditions and this position needs to be maintained and improved continuously (sustainable).Based on these facts the focus of this research is to explore simultaneously evaluate teacher competence (pedagogic competence, personality, professional and social) educational program students field experience (PPLK) PAI Prodi in the teacher's perspective pamong school / madrasah FITK partner UIN Raden Fatah Palembang. In this case performs a search view / response (response) and expectations (expectation) or conduct (cross check) to the field against the PPLK student teacher competence, especially students PPLK Prodi PAI. The question is whether the students PPLK Prodi PAI has the ability or competence in performing qualified practice in the field? In other words, if the student PPLK PAI Prodi has competence as required by the Law on Teachers and Lecturers and government regulation associated with it? And what the teacher's expectations partner school officials to increase student teacher competence PPLK Prodi PAI FITK UIN Raden Fatah? The answers to these important questions to be explored in order to know how exactly the professionalism and competence of students PPLK Prodi PAI in PPLK their duties at school / madrasah partner.This research approach is qualitative research explorative, ie digging as much data as possible through in-depth interviews and observation (participant observation) related to the competence of teacher students PPLK Prodi PAI FITK UIN Raden Fatah and expectations of teachers tutor school / madrasah partner for the competence of teacher students PPLK Prodi PAI FITK UIN Raden Fatah to be constructed as a picture of the ideal model of graduates deemed appropriate quality standards and the expectations of the PAI LPTK (stakeholders). As the primary source of this study was composed of teachers tutor informant who comes MAN, MAS, and SDIT Private High School who had been a school / madrasah FITK partner UIN Raden Fatah. The informant retrieval tailored to the needs of data to be extracted and focus on issues that were analyzed.Based on data analysis can be concluded that students PPLK Prodi FITK PAI already meet the minimum standards (not disappoint) teacher competence. However, efforts to increase still needs to be done to achieve the maximum standard (satisfactory). Based on the answers of informants and the findings of this research, a lot of things that need to be evaluated and repaired by anyone FITK particularly Prodi PAI to improve the competence of teacher students Prodi PAI, ranging from increased knowledge, technical skills, strengthening governance and deepening of the material field of expertise (PAI) to reform giving assignments parenting courses to lecturers appropriate field of expertise and experience (not professors who are still amateur) as well as the need to involve practitioners (teachers professional) parenting courses that are directly related to the competence of jocularity and practice activities / arena experience learning real school / madrasah. Some things that determine the quality of the graduates of teacher competence (output) PAI Prodi FITK UIN Raden Fatah in the present and future.